Penerapan Statistical Process Control untuk Mengetahui Minat Remaja dalam Menggunakan Sepeda Motor Listrik - Andika, Yanwar Surya; Taufik Hidayat; Wahyuningsih, Utami; Rasyidi, Lili; Anggraini, Novia (Metode : Jurnal Teknik Industri, 2025)
The Indonesian government in the National Energy General Plan (RUEN) targets the number of electric vehicles to be 2,200 four-wheeled vehicles and 2.1 million two-wheeled vehicles which must be achieved at least by 2050. Currently, the number of motorized vehicles that are widely used is motorbikes, because the price is relatively cheap, can penetrate traffic jams and use less fuel when compared to other motorized vehicles. Electric motorbikes are an alternative that can reduce the impact on the environment and support government programs in achieving the RUEN target. This study aims to determine the interest of teenagers in using electric motorbikes. By conducting a survey of 144 teenagers based on 4 aspects, namely Environmentally friendly, price, infrastructure availability and operational costs. After the survey was collected, a statistical test of Validity, Reliability and normality was carried out to determine the level of accuracy of the survey data and the results were Valid, Reliable Questionnaires but the data was not normally distributed. Then by using one of the tools in Statistical Process Control, namely the Pareto Diagram which has a rule of 80: 20, the results showed that Respondents realized that electric motorbikes were more environmentally friendly than motorbikes with gasoline fuel. However, in terms of price, respondents have not yet influenced them in buying electric motorbikes. While in terms of infrastructure availability, respondents also considered it inadequate. Meanwhile, in terms of operational costs, respondents also did not influence their interest in buying.